Cosmic ray ensembles as signatures of ultra-high energy photons interacting with the solar magnetic field. Issue 3 (1st March 2022) - ,; Dhital, N.; Homola, P.; Alvarez-Castillo, D.; Góra, D.; Wilczyński, H.; Almeida Cheminant, K.; Poncyljusz, B.; Mędrala, J.; Opiła, G.; Bhatt, A.; Łozowski, B.; et al.
Abstract: Propagation of ultra-high energy photons in the solar magnetosphere gives rise to cascades comprising thousands of photons. We study the cascade development using Monte Carlo simulations and find that the photons in the cascades are spatially extended over millions of kilometers on the plane distant from the Sun by 1 AU. We estimate the chance of detection considering upper limits from current cosmic rays observatories in order to provide an optimistic estimate rate of 0.002 events per year from a chosen ring-shaped region around the Sun. We compare results from simulations which use two models of the solar magnetic field, and show that although signatures of such cascades are different for the models used, for practical detection purpose in the ground-based detectors, they are similar.